2010
DOI: 10.1002/ffj.1977
|View full text |Cite
|
Sign up to set email alerts
|

Character impact odorants from wild mushroom (Lactarius hatsudake) used in Japanese traditional food

Abstract: The components of the volatile oil from wild mushroom (Lactarius hatsudake), used in Japanese traditional food, were analysed and quantifi ed for the fi rst time by capillary GC and GC-MS. Seventy-six components were separated from the oil and of these 71 components were identifi ed. The main components of the oil were oxidized sesquiterpenes [cisisolongifolanone (624.9 μg/100 g), α-cedrene epoxide (578.7 μg/100 g), humulene epoxide III (453.9 μg/100 g), clovane (425.4 μg/100 g)], aliphatic acids [linoleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In addition, some heterocyclic and aromatic compounds have been identified in some Pleurotus mushrooms. Furan is a heterocyclic compound reported in many mushroom species . All six Pleurotus mushrooms contained 2‐pentyl‐furan which provided the earthy and meaty odor and the content ranged from 0.09% to 0.34%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some heterocyclic and aromatic compounds have been identified in some Pleurotus mushrooms. Furan is a heterocyclic compound reported in many mushroom species . All six Pleurotus mushrooms contained 2‐pentyl‐furan which provided the earthy and meaty odor and the content ranged from 0.09% to 0.34%.…”
Section: Resultsmentioning
confidence: 99%
“…Furan is a heterocyclic compound reported in many mushroom species. 32 All six Pleurotus mushrooms contained 2-pentyl-furan which provided the earthy and meaty odor and the content ranged from 0.09% to 0.34%. It has been reported that the 2-pentyl-furan and other furan compounds could be formed in the course of the Maillard reaction during the thermal processing of mushrooms.…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Most of the volatiles were identified by matching their MS spectra and linear retention indices (RI) on Rtx‐5MS column to those of standards . 2‐Ethylfuran, hexanal, ethyl 2‐methylbutyrate, cis‐β ‐ocimene, trans‐β ‐ocimene, β ‐pinene, octanal, linalool, nonanal, decanal, geranial, trans ‐nerolidol, cis ‐3‐hexen‐1‐ol, geraniol, 2‐heptanone, benzaldehyde, cymene, isopentyl butyrate, trans‐ limonene oxide, cis ‐3‐hexenyl isobutanoate, methyl salicylate, cis ‐3‐hexenyl hexanoate, hexyl hexanoate, cis‐ geranylacetone and butylated hydroxytoluene were quantified according to their respective calibration curves using selective ion monitoring (SIM) mode.…”
Section: Methodsmentioning
confidence: 99%
“…Oleo Sci. 63, (6) 577-583 (2014) 581 hatsudake 19 . However, in the VO of B. leucomelas, furan-containing compounds such as furfral, furfuryl alcohol, 2-acetylfuran, 5-methylfurfural, 2-pentylfuran, furfuryl acetate, and 2-hexylfuran were identified.…”
Section: Characterization Of Volatile Components and Odor-active Compmentioning
confidence: 99%